USAGE OF GRAPHS TO GENERATE BASIC ELEMENTS OF FRACTALS THAT CAN BE USED IN REPRESENTING A PERSON’S LIFE - Shah, Pratik; Modani, Snehil; Paranjape, Shardul (European Scientific Journal, ESJ, 2013)
﻿Fractals are geometrical figures that maintain constant behavior in any segment or portion of its figure. These fractals have been proven to be good models to represent complex data so that we can manipulate to make it simple. One such data is representation of a person’s life right down the daily activities. Any person’s life is a repetition of daily lives and since fractals are embedded with the basic principle of recursion in patterns they promise to be suitable models to help represent a person’s life. But these fractals are complex structures formed out of simple structures and these simple structures can be generated or are generated from polygons. Using graphs the basic repetitive pattern can be encoded and then that pattern can be duplicated on larger scales to get the bigger picture or the manipulated data. This paper deals with the procedure of using graphs to encode basic fractal patterns that can help us encode a person’s life in one or a few figure.